Suriname : A Case Study of High Inflation - Shah, Sukhdev (IMF Working Papers; Working Paper, 1999)
Suriname recently went through a period of destabilizationthat that bordered on hyperinflation. The country's experience provides a good illustration to study the genesis and dynamics of high inflation and includes some unusual phenomena, such as a monetary overhang, an eight-tiered exchange rate, and inflationary gold purchases by the central bank. High inflation also had a significant impact on the real economy. This paper compares the experience of Suriname with other countries discussed in the recent stabilization literature. It finds strong evidence of intertemporal demand effects, which occurred as the public reacted to the temporary bout of high inflation.